Pulse tunable SiGeSn/GeSn multi-quantum-well microdisk lasers - Seidel, L.; Liu, T.; Concepcion, O.; Spirito, D.; Benkhelifa, A.; Kiyek, V.; Schulze, Jörg; Marzban, B.; Capellini, G.; Witzens, J.; Grützmacher, D.; Buca, D.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
This paper reports on SiGeSn/GeSn multi-quantum-well microdisk lasers. The fabrication of the devices includes a selective under-etching step, which enhances the guiding of the whispering gallery modes inside the cavity. Lasing occurs under different electrical pumping conditions with a very low threshold current and for long, quasi-continuous wave pulses compared to previously reported GeSn-based microdisk lasers. Furthermore, the lasing threshold current is reduced by a factor of ten compared to similar double-heterostructure devices.
CRIS-Team Scopus Importer:2024-11-01
Keywords: GeSn; Laser; Microdisk; Multi-Quantum-Well; SiGeSn